Extracellular CIRP Promotes GPX4-Mediated Ferroptosis in Sepsis - Shimizu, Junji; Murao, Atsushi; Nofi, Colleen; Wang, Ping; Aziz, Monowar (Frontiers in Immunology, 2022)
Sepsis is characterized by life-threatening organ dysfunction caused by a dysregulated host response to infection. Extracellular cold-inducible RNA-binding protein (eCIRP) is a damage-associated molecular pattern (DAMP) that promotes inflammation and induces cell death via apoptosis, NETosis, and/or pyroptosis. Ferroptosis is a form of regulated cell death characterized by the accumulation of lipid peroxide on cellular membranes. We hypothesize that eCIRP induces ferroptosis in macrophages and lung tissue during sepsis. RAW 264.7 cells stimulated with recombinant murine (rm) CIRP significantly decreased the expression of glutathione peroxidase 4 (GPX4), a negative regulator of ferroptosis, and increased lipid reactive oxygen species (ROS) in a TLR4 dependent manner. In TLR4-/- peritoneal macrophages, depression of GPX4 expression and increase in lipid ROS levels were attenuated after rmCIRP-treatment compared to WT macrophages. rmCIRP also induced cell death in RAW 264.7 cells which was corrected by the ferroptosis inhibitor, ferrostatin-1 (Fer-1). Intraperitoneal injection of rmCIRP decreased GPX4 expression and increased lipid ROS in lung tissue, whereas the increase of lipid ROS was reduced by Fer-1 treatment. GPX4 expression was significantly decreased, while malondialdehyde (MDA), iron levels, and injury scores were significantly increased in lungs of WT mice after cecal ligation and puncture (CLP)-induced sepsis compared to CIRP-/- mice. Treatment with C23, a specific eCIRP inhibitor, in CLP mice alleviated the decrease in GPX4 and increase in MDA levels of lung tissue. These findings suggest that eCIRP induces ferroptosis in septic lungs by decreasing GPX4 and increasing lipid ROS. Therefore, regulation of ferroptosis by targeting eCIRP may provide a new therapeutic approach in sepsis and other inflammatory diseases.